Pengaruh Penggunaan Media Visual Buku AKM Terhadap Hasil Literasi Numerasi Siswa SDIT Al-Hikmah Pangkep Kecamatan Pangkajene Kabupaten Pangkajene dan Kepulauan - Mahdawanty Mahdawanty; Badruddin Kaddas; Syarifah Nur Fajrin; Nur Syam; Sri Hastati (STKIP Andi Matappa Pangkep, 2022)
The aim of the researcher in this study is to find out whether there is an effect of using the AKM book visual media on the numeracy literacy learning outcomes of SDIT Al-Hikmah Pangkep students, Pangkajene District, Pangkajene Regency and Islands. This research method uses quantitative methods. This type of research is pre-experimental research. The type of experiment used is One Group Pretest-Posttest. This type of research was measured using a pretest which was conducted before being given treatment and a posttest which was conducted after being given treatment. In student learning outcomes, students get a score of -7.743 < 2.160 based on the results of posttest data calculations using independent t-test.